Long-term survival of asexual Zymoseptoria tritici spores in the environment - Kay, WT; O’Neill, P; Gurr, SJ; Fones, HN (BioMed Central, 2024)
Background: The fungal phytopathogen Zymoseptoria tritici, causal agent of the economically damaging Septoria tritici blotch of wheat, is different from most foliar fungal pathogens in that its germination occurs slowly and apparently randomly after arrival on the leaf surface and is followed by a potentially prolonged period of epiphytic growth and even reproduction, during which no feeding structures are formed by the fungus. Thus, understanding the cues for germination and the mechanisms that underpin survival in low-nutrient environments could provide key new avenues for disease control. Results: In this work, we examine survival, culturability and virulence of spores following transfer from a high nutrient environment to water. We find that a sub-population of Z. tritici spores can survive and remain virulent for at least 7 weeks in water alone, during which time multicellular structures split to single cells. The fungus relies heavily on stored lipids; however, if cell suspensions in water are dried, the cells survive without lipid utilisation. Changes in gene expression in the first hours after suspension in water reflect adaptation to stress, while longer term starvation (7 days) induces changes particularly in primary metabolism and cytochrome P450 (CYP) gene expression. Importantly, we also found that Z. tritici spores are equally or better able to survive in soil as in water, and that rain-splash occurring 49 days after soil inoculation can transfer cells to wheat seedlings growing in inoculated soil and cause Septoria leaf blotch disease. Conclusions: Z. tritici blastospores can survive in water or soil for long periods, potentially spanning the intercrop period for UK winter wheat. They rely on internal lipid stores, with no external nutrition, and although a large proportion of spores do not survive for such an extended period, those that do remain as virulent as spores grown on rich media. Thus, Z. tritici has exceptional survival strategies, which are likely to be important in understanding its population genetics and in developing novel routes for Septoria leaf blotch control.